MENUMBUHKAN KARAKTER WIRAUSAHA GENERASI MUDA MELALUI PEMANFAATAN KERAJINAN TANGAN - Damanik, Dennys Paulus Parlindungan; Simanjunak, Demak Claudia Yosephine; Angelia, Nia; Purnasari, Nina; Malau, Yois Nelsari (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
Entrepreneurial character plays a crucial role in shaping a creative, innovative, and independent young generation. One effective way to cultivate this character is through the utilization of handicrafts. This community service activity explores the impact of handicrafts, specifically through direct training in making tumbler bags, in fostering entrepreneurial characteristics among young people. Conducted at SMA Pangeran Antasari, located on Jalan Veteran No. 1060/19, Helvetia, Labuhan Deli District, Deli Serdang Regency, North Sumatra, this initiative demonstrates that involvement in handicraft-making encourages self-reliance, creativity, and economic awareness—essential traits for future entrepreneurs. By leveraging handicrafts as a medium for entrepreneurship, young people can develop valuable skills that empower them to build sustainable businesses and contribute to economic growth.